Infilling streamflow data using HEC_HMS - Hong, Kee An; Hong, Jer Lang; Ibrahim, Izihan; Hakim, Nur Wajihah (2020)
A set of quality control streamflow data is always required in the planning, design and management of water resources projects. Although every effort has been made by the authority in the collection of complete and continuous hydrological data such as rainfall and streamflow, gaps and incomplete data sets with inadequate length are always encountered, as is always the case. These can be due to faulty field instruments, the occurrence of natural disasters and other reasons. Over the years, various techniques have been developed to infill the missing data, especially the streamflow data. These techniques include regression analysis ,rainfall runoff modelling and the use of artificial neural networks(ANN) data driven models. In this study, the HEC-HMS model is used to simulate long term daily streamflow of Sg Melaka. The process involved using recorded flow and rainfall data of 1989-1992 to calibrate the model and the model validation using records of 1985-1986. Results show that the model can be used to estimate the flows of Sg Melaka once properly calibrated. This is also shown in the results of flow duration curves. From this study, it can be concluded that missing flows of Sg Melaka can be infilled using the HEC-HMS moel and daily rainfall records in the basin. Streamflow records can be extended if complete rainfall records are available for periods where no streamflow records are available.